The determinants of consumer's intention towards e-shopping among teachers at SMK Aminuddin Baki / Asdilla Ahmad - Ahmad, Asdilla (2016)
E-shopping (on-line shopping) is increasingly becoming most popular in Malaysia by supplanting the traditional store shopping behavior of the large number of customers. The study is focusing on consumer's intention towards e-shopping among teachers at SMK Aminuddin Saki prepared for final project paper in completion of the courses in BSA (Hons) Finance. The data were collected from those Malaysian consumers who some experience on e-shopping. There are five independent variables (IV). Therefore, this research is aims to investigate whether the products and service attributes (PS), web characteristics (WC), perceived risk (PR), perceived pricing (PP) and perceived benefits (PB) have significant influence on consumer's intention towards e-shopping (Cl) among teachers at SMK Aminuddin Saki. A total of 106 teachers at SMK Aminuddin Saki completed the self administered questionnaire of intention towards e-shopping. The respondents come from various income, so the result obtain should be generalized. The findings show that all the PS, WC, PR, PP and PB have positive relationship with Cl. Therefore, a better understanding of the factors that influence e-shopping intention would help in planning better marketing strategies in targeted segments.